PENGARUH LINGKUNGAN LAPANGAN TERBANG PADA PERENCANAAN PANJANG LANDASAN DENGAN STANDAR A.R.F.L. - Dwi Sri Wiyanti (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2006)
Abstract In planning a new airport or developing an airport to an internasional airport, minimum requrements both land condition and technical requirements such as length of runway and the others, need to be met. The requirements are related each other to fulfil the feasibility of an international airport. The factors that throughly crucial in the planning of runway length are, among others, temperature, elevation, runway gradient, surface wind, And runway surface. The standard calculation used to determine length of runway iS called ARFL (Aeroplane Reference Field Length) the length of runway needed by an aircraft in line with its capacity according to the calculation of the manufacturer of te aircraft. Every ARFL has correction factors such as Fe (‘Correction jör Elevation), Ft (Correction for Temperature) , and Fg (Correction for Gradient). However, the factors that influence the length of runway are only estimation. Key words: runway length, runway gradient, runway surface.